2015
DOI: 10.1128/aac.03944-14
|View full text |Cite
|
Sign up to set email alerts
|

The Investigational Agent E1210 Is Effective in Treatment of Experimental Invasive Candidiasis Caused by Resistant Candida albicans

Abstract: cThe in vitro and in vivo activity of the inositol acyltransferase inhibitor E1210 was evaluated against echinocandin-resistant Candida albicans. E1210 demonstrated potent in vitro activity, and in mice with invasive candidiasis caused by echinocandinresistant C. albicans, oral doses of 10 and 40 mg E1210/kg of body weight twice daily significantly improved survival and reduced fungal burden compared to those of controls and mice treated with caspofungin (10 mg/kg/day). These results demonstrate the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 17 publications
3
28
0
Order By: Relevance
“…This leads to pleotropic effects, including compromised cell wall integrity, and a reduction in fungal virulence attributes, including biofilm and germ tube formation, all of which ultimately contribute to severe fungal growth defects. APX001A/APX001 has potent broad in vitro and in vivo activity against major fungal pathogens, including Candida, Cryptococcus, Aspergillus, Scedosporium, and Fusarium strains, regardless of their azole resistance and echinocandin resistance, which is consistent with the distinct mechanism of action (16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
supporting
confidence: 52%
“…This leads to pleotropic effects, including compromised cell wall integrity, and a reduction in fungal virulence attributes, including biofilm and germ tube formation, all of which ultimately contribute to severe fungal growth defects. APX001A/APX001 has potent broad in vitro and in vivo activity against major fungal pathogens, including Candida, Cryptococcus, Aspergillus, Scedosporium, and Fusarium strains, regardless of their azole resistance and echinocandin resistance, which is consistent with the distinct mechanism of action (16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
supporting
confidence: 52%
“…Furthermore, APX001 has excellent, broad-spectrum potency with antifungal activity in vitro against Candida spp. and Aspergillus spp., and can provide antifungal activity against some drug-resistant yeasts and moulds 77,78 . It even has potent antifungal activity in vitro against moulds that are difficult to treat, such as Fusarium spp.…”
Section: New Agents In Developmentmentioning
confidence: 99%
“…Importantly, the compound seems to be fungal specifi c and does not inhibit mammalian GPI inositol acylase PIG-W activity ( 194 ). In vivo effi cacy of this agent has been demonstrated after oral administration in a murine model against candidiasis, aspergillosis, and fusariosis ( 189,195 ). Another group reported that a different compound, gepinacin, also inhibited Gwt1p activity ( 196 ).…”
Section: Downloaded Frommentioning
confidence: 99%